A bio-inspired flapping wing rotor of variant frequency driven by ultrasonic motor - Chen, Si; Wang, Le; Guo, Shijun; Zhao, Chunsheng; Tong, Mingbo (MDPI, 2020)
By combining the flapping and rotary motion, a bio-inspired flapping wing rotor (FWR) is a unique kinematics of motion. It can produce a significantly greater aerodynamic lift and efficiency than mimicking the insect wings in a vertical take-off and landing (VTOL). To produce the same lift, the FWR’s flapping frequency, twist angle, and self-propelling rotational speed is significantly smaller than the insect-like flapping wings and rotors. Like its opponents, however, the effect of variant flapping frequency (VFF) of a FWR, during a flapping cycle on its aerodynamic characteristics and efficiency, remains to be evaluated. A FWR model is built to carry out experimental work. To be able to vary the flapping frequency rapidly during a stroke, an ultrasonic motor (USM) is used to drive the FWR. Experiment and numerical simulation using computational fluid dynamics (CFD) are performed in a VFF range versus the usual constant flapping frequency (CFF) cases. The measured lifting forces agree very well with the CFD results. Flapping frequency in an up-stroke is smaller than a down-stroke, and the negative lift and inertia forces can be reduced significantly. The average lift of the FWR where the motion in VFF is greater than the CFF, in the same input motor power or equivalent flapping frequency. In other words, the required power for a VFF case to produce a specified lift is less than a CFF case. For this FWR model, the optimal installation angle of the wings for high lift and efficiency is found to be 30° and the Strouhal number of the VFF cases is between 0.3–0.36. View Full-Text
Keywords: flapping wing rotor; ultrasonic motor; variable actuation frequency